Análisis del comportamiento de las tarifas de impuesto predial unificado a la zona rural del municipio de Zetaquira - Boyacá (2023)
One of the main problems that arise in the property tax is the appraisal of rural properties, which lack an adequate valuation for the productivity of the land, and are real estate properties that are built and generate a higher value. Therefore, the property tax comes from the cadastral appraisal as the taxable base of this tax.